Differential diagnosis of suspected multiple sclerosis: an updated consensus approach - Solomon, Andrew J; Arrambide, Georgina; Brownlee, Wallace J; Flanagan, Eoin P; Amato, Maria Pia; Amezcua, Lilyana; Banwell, Brenda L; Barkhof, Frederik; Corboy, John R; Correale, Jorge; Fujihara, Kazuo; Graves, Jennifer; et al. (Lancet neurology, 2023)
Accurate diagnosis of multiple sclerosis requires careful attention to its differential diagnosis—many disorders can mimic the clinical manifestations and paraclinical findings of this disease. A collaborative effort, organised by The International Advisory Committee on Clinical Trials in Multiple Sclerosis in 2008, provided diagnostic approaches to multiple sclerosis and identified clinical and paraclinical findings (so-called red flags) suggestive of alternative diagnoses. Since then, knowledge of disorders in the differential diagnosis of multiple sclerosis has expanded substantially. For example, CNS inflammatory disorders that present with syndromes overlapping with multiple sclerosis can increasingly be distinguished from multiple sclerosis with the aid of specific clinical, MRI, and laboratory findings; studies of people misdiagnosed with multiple sclerosis have also provided insights into clinical presentations for which extra caution is warranted. Considering these data, an update to the recommended diagnostic approaches to common clinical presentations and key clinical and paraclinical red flags is warranted to inform the contemporary clinical evaluation of patients with suspected multiple sclerosis.